Wild cherry Prunus microcarpa: its phytochemical, antioxidant, enzyme inhibitory, anti-inflammatory, and acute toxicity approaches - A.j. Jabbar, Ahmed; Abdul-Samad Ismail, Parween (Italian Journal of Food Science, 2025)
Therapeutic plants are potentially a great renewable biomolecule source with fewer downsides than synthetic chemicals. Prunus microcarpa Boiss. is a wild fruity plant prepared by hydro-distillation and consumed as a traditional remedy for many health defects. The study investigates the phytoconstituents, antioxidant, anti-inflammatory, and acute toxicity effects of methanolic extracts of P. microcarpa fruits and stems plus pedicles (MEPMF and MEPMSP). The total phenolics, flavonoids, anthocyanins, and tannins were spectrophotometrically estimated. The enzyme inhibitory action (against α-amylase and α-glucosidase), antioxidant potentials (using five different assays), and anti-inflammatory potentials (using the egg albumin denaturation procedure) were determined. Phytochemical profiling revealed increased total phenolics (76.34 and 121.45 mg gallic acid equivalent/g extract), flavonoids (210.30 and 18.93 mg GAE/g extract), anthocyanin (176.23 and 149.34 mg cyanidin 3-glucoside equivalent/g extract), and tannins (112.39 and 64.87 mg GAE/g extract) in MEPMF and MEPMSP, respectively. MEPMF had higher antioxidant potentials (130.83 and 117.12 mg TEs/g–1 extract in ABTS and DPPH assays, respectively) and higher reducing power actions (413.40, 141.23, and 97.62 mg TEs/g–1 extract in phospho-molybdenum, CUPRAC, and FRAP assays, respectively) than that of MEPMSP. MEPMF showed better inhibitory actions against α-amylase (IC50; 6.70 mg/mL), α-glucosidase (IC50; 5.72 mg/mL), and protein denaturation (IC50; 53.78 mg/mL) than that (IC50; 7.53, 6.28, and 84.42 mg/mL, respectively) of MEPMSP. According to biochemical evaluation, both extracts (2 and 5 g/kg) showed nontoxic effects in a two-week animal trial. In this first detailed record on P. microcarpa, the species exhibited numerous biological potentials attributed to its rich phytoconstituents, which also backed up its ethnomedicinal use.